The Role of Digital Technologies in Enhancing Visual Arts Education for Middle School Students - Gadoyev Ibrohim Niyozovich (SCIENCE AND CULTURE: INNOVATIONS OF THE 21ST CENTURY, 2025)
Abstract: This article investigates the role of digital technologies in enhancing visual arts education for middle school students. It examines various pedagogical approaches, interactive methods, and multimedia tools to foster creativity, artistic skills, and aesthetic appreciation. The study highlights the effectiveness of integrating digital platforms, virtual galleries, and design software in developing students’ artistic competencies and independent creative thinking.